A systematic review of hope as a psychosocial factor among gifted students in the Asian context - Ahmad Rosdi, Ahmad Azrul Afeze; Ahmad, Nor Aniza; Burhanuddin, Nur Aimi Nasuha (Human Resource Management Academic Research Society, 2024)
A systematic literature review was conducted to explore the role of hope as a psychosocial factor among gifted students within the Asian context, aiming to provide a comprehensive understanding of its impact on their well-being and academic performance. Five online databases (SAGE, Scopus, Taylor & Francis Online, Elsevier and WILEY) were systematically searched to identify relevant articles published between 2016 and 2024. Most studies in the review employed qualitative methods in order to have a deeper understanding about the element of hope among gifted students. This review highlights how hope is crucial for gifted students who often face unique challenges. The review also identifies research gaps, including the need for more longitudinal studies and comparative research to understand how hope among gifted students differs from their non-gifted peers. The insights gained from this review emphasises the importance of incorporating hope-focused interventions in educational and psychological support frameworks to enhance the holistic development of gifted students in Asia.